Human Thelaziasis: Emerging Ocular Pathogen in Nepal. (15th September 2018) - Sah, Ranjit; Khadka, Shusila; Adhikari, Mahesh; Niraula, Reema; Shah, Apoorva; Khatri, Anadi; Donovan, Suzanne
Abstract: Thelaziasis is an ocular arthropod-borne, zoonotic disease of the eye infecting the conjunctival sac, lacrimal duct, and lacrimal gland caused by a nematode of the genus Thelazia . We report the first case of human ocular thelaziasis in Nepal in a 6-month-old child from a Rukum district, Nepal. The infant presented with conjunctivitis, and his visual acuity and dilated fundal examination were normal. A total of 6 worms were removed for identification. Collected nematodes were identified based on morphological keys as Thelazia callipaeda . The patient's symptoms improved after removal of the nematodes.